Humic Acid-Modified Magnetite Nanoparticles for Removing [AuCl4]− in Aqueous Solutions - Soerja Koesnarpadi Koesnarpadi; Nanang Tri Widodo; Acmad Maulana Maulana (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Humic acid-modified magnetite nanoparticle (MnP-HA) has been synthesized using the co-precipitation method and applied for removal of [AuCl4]−. Modifying of MnP-HA was prepared with the mass ratio of MnP-HA=10:1 and 10:3. The HA was extracted from peat soil of Sambutan Village, East Kalimantan, Indonesia, by the recommended procedure of the International Humic Substances Society (IHSS). The saturation magnetization of MnP-HA was decreased compared to unmodified MnP. The interaction between MnP and HA was occurred due to the chemical bond between Fe from MnP with the carboxylic group from HA. The coating HA on the surface of MnP unchanged the formation of the crystal structure of MnP and increased the particle size. The optimum removal of [AuCl4]− on MnP and MnP-HA materials was optimum at pH 3.0. The Langmuir isotherm model with sorption capacity was 0.23, 4.85, and 4.65 mol g–1 for MnP, MnP-HA=10:1, and 10:3, respectively. Using a pseudo-second-order equation, the degradation of the kinetics model of [AuCl4]− on MnP, MnP-HA=10:1 and 10:3 with adsorption rate constant (k) were 0.02, 0.07, and 0.06 g.mol min–1.